COMPARISON OF POCT AND HEMATOLOGY ANALYZER METHODS FOR HEMOGLOBIN LEVEL EXAMINATION IN SECOND TRIMESTER PREGNANT WOMEN AT TUMPANG HEALTH CENTER - fitria, diva anggi (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Hemoglobin is a component of the protein molecule in erythrocyte cells that distributes oxygen (O2) throughout the body. Hemoglobin contains iron which makes blood red. HB levels are a supporting examination that helps establish a diagnosis as a reflection of the body's reaction to a disease and as an indication of the progress of therapy for anemia sufferers and other diseases. Method: This type of research is descriptive research with a cross sectional design. The sample collection technique used the Accidental Sampling technique with a sample population of 22 pregnant women in the second trimester at the Tumpang Community Health Center. Results: The results of research on hemoglobin levels using the POCT method and Hematology Analyzer using the dependent T test showed a significant comparison of p value 0.01 (0.05). The average POCT Hb level result was 1.55 g/dl and the average hematology analyzer Hb level result was 1.82 g/dl. The Hematology Analyzer method is more accurate because the average result obtained is higher than POCT.Conclusion :Suggestions for further research can be used Different samples and a larger number of samples require comparative examination of HB levels using other methodssahli, cyanmethemoglobin, and tallquist.